Examining the direct and indirect effects of trust in motivating COVID-19 vaccine uptake. Issue 7 (July 2022) - Liu, Sixiao; Chu, Haoran
Abstract: Objectives: This study aims to investigate how trust in healthcare providers, public health agencies, politicians, and pharmaceutical companies shaped people's attitudes and behavioral intention associated with COVID-19 vaccination, directly and indirectly via the mediation of vaccine evaluation and emotions. Methods: A two-wave longitudinal survey ( N  = 534) was employed in late 2020 and early 2021 to assess the direct and indirect relationships between trust on people's attitude toward the COVID-19 vaccine, vaccination intention, and actual vaccine uptake. Results: Results show that trust was positively associated with attitude toward the COVID-19 vaccines and vaccination intention, both directly and indirectly via the mediation of vaccine evaluation, hope, and anger. Vaccination intention also mediated trust's influence on vaccine uptake. Conclusion: Trust in health providers, vaccine manufacturers, and public health agencies are vital to public acceptance of the COVID-19 vaccine. Practice implications: Healthcare providers and vaccine manufacturers may serve as the most effective source to communicate COVID-19 vaccine-related information. Trusted health communicators need to highlight the effectiveness and safety of the vaccine while maintaining a positive tone. Highlights: Trust in healthcare providers, agencies, and pharmaceutical companies increased vaccination. Perceived effectiveness and safety concern mediated trust's effects on vaccine uptake. Hope mediated trust's influence on vaccine uptake intention. Healthcare providers may be the most effective sources of information about COVID-19 vaccine.